The Role of Supervisory Consultants on Occupational Safety and Health (K3) for Workers in the Lebak Regency School Infrastructure Rehabilitation and Renovation Project - Hanafi; Yanti Fatmariyanti (PT FORMOSA CENDEKIA GLOBAL, 2022)
Construction activities are an important element in development, which can cause various impacts, one of which concerns work safety and environmental aspects, so they must be managed with due observance of applicable K3 standards and provisions. This study aims to determine the role of the Supervisory Consultant on Occupational Safety and Health for Workers in the Lebak Regency School Rehabilitation and Renovation Project. The research method uses SPSS (Statistical Package for the Social Sciences) which will test the validity and reliability of the data. Primary research data was obtained by filling out questionnaires to 35 respondents which showed a result of 57.1% or 20 worker respondents who had not implemented OSH in the project. This is due to the lack of workers' knowledge of the importance of OSH. Based on the results of the Chi Square statistical test, a significant (significant) relationship was obtained which was expressed by a significance value of p value 0.000 which was less than 0.005 (p value <0.05)